Jus Apel Manalagi (Malus Sylvestris Mill) menghambat pertumbuhan Streptococcus mutans in vitro - Dewi Anggraini; I Dewa Made Sukrama; Ni Kadek Fiora Rena Pertiwi (Bali Dental Journal, 2018)
Background: Manalagi apple (malus sylvestris mill) is a popular fruit consumed by the people of Indonesia. Objective: This study aims to determine the inhibition of manalagi apple juice on the growth of streptococcus mutans with a concentration of 60%, 80%, 100%. Methods: This study was an experimental study using disc diffusion method by using 5 samples in each treatment groups namely manalagi apple juice concentration of 60%, 80%, 100%, the positive control group (vancomicyn 30Âµg), and a negative control group (aquades sterile) data analysis using kruskal-wallis test and mannwhitney test. Results: From the Shapiro-wilk test result showed that the data were normally distributed to a concentration of 80% and 30Î¼g vancomycin with p = 0.314 and not normally distributed to a concentration of 60% with a value p = 0.006 and a concentration of 100% with a value of p = 0.000. This study shows that manalagi apple juice at all concentrations have antibacterial activity against the growth of streptococcus mutans. 100% concentration is the concentration that is still able to inhibit the growth of Streptococcus mutans. Conclusions: The conclusion of this study proves that the manalagi apple juice have antibacterial activity against the growth of streptococcus mutans.